2020
DOI: 10.1016/j.jcrc.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid implementation of a mobile prone team during the COVID-19 pandemic

Abstract: Purpose The coronavirus disease 2019 (COVID-19) is associated with high rates of acute respiratory distress syndrome (ARDS). Prone positioning improves mortality in moderate-to-severe ARDS. Strategies to increase prone positioning under crisis conditions are needed. Material and methods We describe the development of a mobile prone team during the height of the crisis in New York City and describe characteristics and outcomes of mechanically ventilated patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
(19 reference statements)
2
25
0
2
Order By: Relevance
“…To date, several groups have approached the problem regarding the creation of a dedicated team in order to better manage the high number of pronations in critically ill COVID-19 patients [ 19 , 21 , 22 , 30 , 31 ]. However, no study reported data concerning the impact of a dedicated team that avails itself of the support of physiotherapists on the incidence of pronation-induced complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several groups have approached the problem regarding the creation of a dedicated team in order to better manage the high number of pronations in critically ill COVID-19 patients [ 19 , 21 , 22 , 30 , 31 ]. However, no study reported data concerning the impact of a dedicated team that avails itself of the support of physiotherapists on the incidence of pronation-induced complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some groups addressed the incidence of pronation-related complications in critically ill COVID-19 patients [ 19 , 20 ]. In this setting, Short et al [ 21 ] reported a clinical benefit in having a specific “pronation team” dedicated to patients’ pronation during the pandemic wave [ 22 ], even though they focused mainly over clinical patients evolution, rather than over the rate of complications related to this delicate procedure.…”
Section: Introductionmentioning
confidence: 99%
“…No unnecessary harm to patients by way of dislodgement of endotracheal airway tubes, arterial and central venous monitoring catheters, and drainage catheters occurred. Doussot et al 28 reported 8.8% position-related complications and Short et al 27 reported catheter dislodgement in 1 patient. Our outcomes stand out from those of other colleagues at facilities with dedicated PTs, in part because of the comprehensive training and post-turn debriefings that were conducted, as well as leadership enculturation of a habit of excellence 24 ; staff were treated with respect, given adequate resources, and shown regular appreciation for their efforts.…”
Section: Discussionmentioning
confidence: 98%
“…Composed of operating room nurses, assistants, and physical therapists who were familiar with critically ill patients and positioning maneuvers, the PT ensured that no additional strain was added to clinical nursing and other bedside clinicians who were already over-burdened with the surge. In a recent article, Short et al 27 supported the importance of familiarity with these skills.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several groups have approached the problem regarding the creation of a dedicated team in order to better manage the high number of pronations in critically ill COVID-19 patients (Cotton et al, 2020;Doussot et al, 2020;Johnson et al, 2021;Ng et al, 2020;Short et al, 2020). However, no studies reported data concerning the impact of a physiotherapy team on the incidence of pronation-induced complications.…”
Section: Discussionmentioning
confidence: 99%